Trade Openness Index: Analysis Model of Indonesia, China, and the United States in Global Economic Dynamics - Sari Febrianti O Pasaribu; Dewi Mahrani Rangkuty; Rusiadi Rusiadi (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the simultaneous effect of trade openness, exports, imports, and inflation on gross domestic product and the simultaneous effect of trade openness, exchange rates, and gross domestic product on inflation in Indonesia, China, and the United States. This study uses a quantitative approach with secondary data (time series) sourced from the World Bank for the period 2014 to 2023. The data analysis technique used is the Two-Stage Least Squares (TSLS) method. The results obtained explain that in equation I, it was found that the variables of trade openness and imports have a significant effect on gross domestic product (GDP) in Indonesia, China, and the United States. Meanwhile, the export and inflation variables did not have a significant effect on gross domestic product (GDP) in Indonesia, China, and the United States. Equation II found that the variables of trade openness, exchange rate, and gross domestic product (GDP) had a significant effect on inflation in Indonesia, China, and the United States.